Academic Supervision Management Based on KOMPAK (Collaborative Active Learning Community) to Improve Learning Quality - Muhammad Mufid; Didi Supriadi (Journal of Creative Power and Ambition (JCPA), 2026)
Academic supervision is a fundamental component of educational management that aims to improve the quality of teaching and learning processes in schools. This study aims to analyze the implementation of academic supervision management based on KOMPAK (Collaborative Active Learning Community) in improving the quality of learning at SD Negeri 1 Wonosobo. The research employs a qualitative descriptive approach to explore how academic supervision is planned, implemented, and evaluated within a collaborative learning framework involving teachers and school leadership. Data were collected through interviews, observations, and documentation, and analyzed using an interactive model consisting of data condensation, data display, and conclusion drawing. The findings show that KOMPAK-based academic supervision is implemented through collaborative activities such as joint lesson planning, peer observation, reflective discussions, and continuous feedback sessions. This model shifts the supervision approach from a traditional evaluative system to a more developmental and participatory process that encourages teacher engagement and professional growth. The results also indicate that the implementation of KOMPAK contributes significantly to improving teacher performance, instructional innovation, and student learning outcomes by fostering a culture of collaboration and reflection within the school.